Evaluating Low Income Families’ self Perception of the Economic Aid Program: The Albanian Case - Lumanaj, Brilanda; Hasi, Sidita (Richtmann Publishing, 2012)
Given the complicated transition in which post communist countries have been going through during their rapiddevelopment, it is important to make sure that concerns of the weakest part of these societies are taken into consideration andnot left on their own fate hidden in the chaotic transition process. This study is an evaluation of Albanian needy families’perceptions of the public Economic Aid program. Qualitative research was based on ten interviews of Economic Aid recipients,male and female baby boomers. They all had children. The findings showed a huge gap between the Economic Aid amount andtheir real expenses and needs. In most cases this gap was covered from black market jobs. Recipients felt extremely poor,inferior, hopeless, and concerned about surviving. The lack of trust in the Economic Aid program in specific and the governmentin general was due to perceived high level of corruption. We recommended a practical framework for restructuring the EconomicAid program in terms of the amount delivered, transparency, employment support, psychological assistance for both parents andchildren, and better medical coverage.